2002
DOI: 10.1097/00024382-200207000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Peroxynitrite Enhances the Ability of Salmonella dublin to Invade T84 Monolayers

Abstract: In the intestine, epithelial cells continually produce and secrete low levels of nitric oxide (NO). Salmonella sp. invade epithelium by responding to environmental stimuli. The aims of this study were to determine the effect of reactive nitrogen intermediates (RNIs) on S. dublin and S. typhimurium growth and invasion of T84 epithelial monolayers. Intracellular NO formation was inhibited by 7-nitroindazole (7-NI) or N(G)-monomethyl-L-arginine, monoacetate (L-NMMA); extracellular NO and peroxynitrite were scaven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In light of the fact that high flux NO seen in pathological situations produces RNS with resultant 3NY formation (Tamir et al. 1993, 1996; Cornish et al. 2002), and cell death (Estevez et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of the fact that high flux NO seen in pathological situations produces RNS with resultant 3NY formation (Tamir et al. 1993, 1996; Cornish et al. 2002), and cell death (Estevez et al.…”
Section: Resultsmentioning
confidence: 99%
“…1a). For the challenge NO dose, we used 10 lM final concentration spermine-NONOate, which donates NO at a higher flux (Cornish et al 2002) of 110 pmol/s (high dose) (Fig. 1a).…”
Section: Physiologically Relevant Nitric Oxide Dosesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that NO at a high flux produces RNS with resultant 3NY formation (Tamir et al. 1993, 1996) and that spermine‐NONOate, unlike DETA‐NONOate, does donate NO at a high flux (Cornish et al. 2002).…”
Section: Resultsmentioning
confidence: 99%
“…1a, cytotoxic). It has been demonstrated that NO at a high flux produces RNS with resultant 3NY formation (Tamir et al 1993(Tamir et al , 1996 and that spermine-NONOate, unlike DETA-NONOate, does donate NO at a high flux (Cornish et al 2002). We asked if pre-treatment of motor neurons with low dose NO induced NO resistance to normally cytotoxic doses of NO (Fig.…”
Section: More Physiologically Relevant Induced Adaptive Resistance Prmentioning
confidence: 99%